Characteristics of younger women Veterans with service connected disabilities - Maynard, Charles (Heliyon, 2019)
OBJECTIVES: There has been an increase in the number of women Veterans with service connected disabilities, which are illnesses or injuries incurred or aggravated during military service. We compared military service and disability characteristics in women and men ≤50 years of age. METHODS: This study included 4,029,672 living Veterans who had at least 1 service connected condition and an active award status as of October 1, 2016. The date of last award as well as demographic, military service, and disability characteristics were obtained from the Veterans Benefits Administration (VBA) VETSNET file. RESULTS: Among 388,947 women Veterans with service connected conditions, almost 60% (n = 231,364) were ≤50 years of age. Roughly 55% of both women and men ≤50 years had a ≥50% combined rating, although there were differences with respect to individual service connected conditions. Women less often had service connected post traumatic stress disorder (23% vs 32%), but more often had major depression (15% vs 7%). While traumatic brain disease was more common in men, migraine headache was much more common in women (32% vs 18%). Less than half had a VA outpatient visit in the previous year. CONCLUSIONS: The findings of significant numbers of younger women with service connected PTSD, depression, or migraine headache should be considered within the context of post deployment health. These findings raise questions regarding outreach to women Veterans who have these conditions, but do not use VA health care.